STUDY THE AFFORD OF STOCKS OF ALMOND KORSCHINSKII AND ORIENTALIS TO SOME PHYSIOLOGICAL TRAITS - Al-Hasan, M. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The study was conducted in order to know the ability of Korschinskii and Orientalis Almonds to tolerance of the drought stress using several levels of water irrigation (100, 75, 50 and 25%) from the field capacity, with several indicators (number of leaves, the thickness of the leaves, root growth).  The results obtained not affected by the stock in the KorschinskiiAlmonds drought stress (255, 242, 220, 198 leaves), while the number of leaves that accompany the burning edges under the influence of droughtstress  inOrientalis Almonds (250, 130, 60, 12 leaves) at levels of  irrigation water (100, 75, 50, 25%) of field capacity respectively. Korschinskii Almond superiority in terms of morale in the thickness of the leaves (0.022, 0.026, 0.026, 0.028 cm) compared with Orientalis Almond (0.024, 0.025, 0.026, 0.026 cm) at levels of irrigation water (100, 75, 50 and 25%) from the field capacity arrangement, which played an important role in tolerance drought stress, and the results obtained showed the superiority of the Korschinskii Almonds length on the main roots (41.15, 43.13, 45.12, 50.1 cm) while of Orientalis Almond (39.5, 40.66, 41.13, 43.16 cm) of irrigation water (100, 75, 50 and 25%) from the field capacity arrangement, which reflected positively on the ability to withstand drought stress.